Impact of Proton Pump Inhibitor Use on Efficacy of Dual Antiplatelet Therapy in Post-PCI Patients: A Meta-Analysis of Randomized Controlled Trials - Shadia , Sajjal; Janjua, Mahnoor Javed; Wandala, Abali; Khan, Wafa; Alauddin, Muhammad Shahid; Abid, Zunaira; Bibi, Tayyaba; Afzal , Mishal (Indus Journal of Bioscience Research, 2025)
Background: Dual antiplatelet therapy (DAPT) is a standard treatment following percutaneous coronary intervention (PCI), significantly reducing ischemic events but increasing gastrointestinal (GI) bleeding risk. Proton pump inhibitors (PPIs) are frequently co-prescribed to mitigate this risk, yet concerns persist regarding potential interactions with P2Y12 inhibitors—particularly clopidogrel—that may compromise cardiovascular outcomes. Objective: The objective of this meta-analysis is to assess the impact of proton pump inhibitor (PPI) use on the efficacy and safety of dual antiplatelet therapy (DAPT) in patients who have undergone percutaneous coronary intervention (PCI). By analyzing data from randomized controlled trials (RCTs), this study aims to determine whether concurrent PPI therapy alters cardiovascular outcomes or provides gastrointestinal protection without compromising antiplatelet effectiveness. Methods: A systematic search of PubMed, Embase, Cochrane Library, and Web of Science identified RCTs comparing DAPT with and without concurrent PPI use in PCI patients. Five RCTs met the inclusion criteria. Primary outcomes included major adverse cardiovascular events (MACE), myocardial infarction (MI), stroke, and GI events. Data were synthesized using a random-effects model, and heterogeneity was assessed via the I² statistic. Results: PPI use was associated with a significantly increased risk of MACE (OR: 1.12; 95% CI: 1.04–1.21), MI (OR: 1.20; 95% CI: 1.10–1.31), and stroke (OR: 1.15; 95% CI: 1.02–1.29), while significantly reducing GI events (OR: 0.75; 95% CI: 0.68–0.83). Subgroup analyses indicated heightened cardiovascular risk in high-risk patients and those on prolonged DAPT or omeprazole. Heterogeneity was low to moderate across outcomes. Conclusion: While PPIs offer substantial GI protection in patients on DAPT post-PCI, their use may elevate cardiovascular risk, particularly with clopidogrel and long-term therapy. These findings support personalized risk-benefit assessment and the cautious selection of PPIs in this patient population.